A fluxional copper acetylide cluster in CuAAC catalysis - Makarem, Ata; Berg, Regina; Rominger, Frank; Straub, Bernd Franz (Angewandte Chemie. International edition, 2015)
A molecularly defined copper acetylide cluster with ancillary N-heterocyclic carbene (NHC) ligands was prepared under acidic reaction conditions. This cluster is the first molecular copper acetylide complex that features high activity in copper-catalyzed azide-alkyne cycloadditions (CuAAC) with added acetic acid even at −5 °C. Ethyl propiolate protonates the acetate ligands of the dinuclear precursor complex to release acetic acid and replaces one out of four ancillary ligands. Two copper(I) ions are thereby liberated to form the core of a yellow dicationic C2-symmetric hexa-NHC octacopper hexaacetylide cluster. Coalescence phenomena in low-temperature NMR experiments reveal fluxionality that leads to the facile interconversion of all of the NHC and acetylide positions. Kinetic investigations provide insight into the influence of copper acetylide coordination modes and the acetic acid on catalytic activity. The interdependence of “click” activity and copper acetylide aggregation beyond dinuclear intermediates adds a new dimension of complexity to our mechanistic understanding of the CuAAC reaction.